Description of the Third-Stage Larva and Puparium of Platycheirus (Carposcalis) chalconota (Philippi) (Diptera: Syrphidae) with New Information About the Trophic Interactions and Larval Habitats - López García, Guillermo Pablo (2022)
In this study, the third-stage larva and puparium of the copper-backed fly, Platycheirus (Carposcalis) chalconota (Philippi, 1865) are fully described using stereomicroscopy and scanning electron microscopy from material collected in peach orchards of central-west Argentina. The immature stages of P. chalconota were compared with the third-stage larva and puparium of the best-studied species in the genus Platycheirus scutatus (Meigen, 1822); as well as with the only known Carposcalis immature stages description available for the Neotropical region namely Platycheirus stegnus (Say, 1829). New data on trophic interactions and larval habitats are given: P. chalconota larvae were found feeding on the aphid’s species Uroleucon sonchi (Linnaeus, 1767) (large sow thistle aphid) and Hyperomyzus lactucae (Linnaeus, 1758) (blackcurrant-sow thistle aphid) in low vegetation as Sonchus oleraceus (common sow thistle); the species was also found feeding on Myzus persicae (Sulzer, 1776) (green peach aphid) in high vegetation as Prunus persicae (L.) Stokes (Peach trees). The third larval stage and puparium of P. chalconota are described and illustrated for the first time improving substantially the knowledge about the immature stages and natural history of Neotropical Platycheirus, constituting also a baseline for future comparative morphological studies. Despite the efficiency of P. chalconota in the biological control of pests has not been assessed, we think that relevant data presented here can be used in pest management of peach orchards and suggest P. chalconota as an excellent candidate for future studies on the life cycle, prey consumption, efficiency, artificial rearing, and its potential importance as pollinators of Peach crops.